Learning innovation through biopreneurship to improve the interest of entrepreneurs of madrasah aliyah students based on boarding school - Deden Ibnu Aqil; Adeng Hudaya; Lusiana Wulansari (Intelektual Pustaka Media Utama, 2020)
The difficulty of entering the workforce requires the world of education to change the paradigm of thinking students from job-seeking cultures become job creators or entrepreneurs. Islamic boarding schools are educational institutions that can provide learning experiences directly to students or students. Islamic boarding school graduates do not all go to college and work immediately while the desire or interest of students for entrepreneurship is still very low. Islamic boarding schools must be able to equip students or santri by inserting learning activities with entrepreneurship education to equip them with skills. The purpose of this study was to determine the success of the implementation of learning innovations through biointpreneurship in increasing interest in entrepreneurship in Islamic boarding schools so as to inspire students to create their own work opportunities with skills in making biotech products in biology. This research is a research development (R and D). The development of learning is oriented towards making biotechnology products by adding entrepreneurial concepts and then experimenting with the experimental class. Data is taken by observation and questionnaire. Data testing techniques using t-paired samples test. The results showed that there was an increase in interest in entrepreneurship from before and after the application of learning with bioentrepreneurship.